Future advances and challenges of nanomaterial-based technologies for electromagnetic interference-based technologies: A review - Karim, S.S. (Academic Press Inc., 2022)
The emerging growth of the electronic devices applications has arisen the serious problems of electromagnetic (EM) wave pollution which resulting in equipment malfunction. Therefore, polymer-based composites have been considered good candidates for better EMI shielding due to their significant characteristics including, higher flexibility, ultrathin, lightweight, superior conductivity, easy fabrication processing, environmentally friendly, corrosion resistive, better adhesion with physical, chemical and thermal stability. This review article focused on the concept of the EMI shielding mechanism and challenges with the fabrication of polymer-based composites. Subsequently, recent advancements in the polymer composites applications have been critically reviewed. In addition, the impact of polymers and polymer nanocomposites with different fillers such as organic, inorganic, 2D, 3D, mixture and hybrid nano-fillers on EMI shielding effectiveness has been explored. Lastly, future research directions have been proposed to overcome the limitations of current technologies for further advancement in EMI shielding materials for industrial applications. Based on reported literature, it has been found that the low thickness based lightweight polymer is considered as a best material for excellent material for next-generation electronic devices. Optimization of polymer composites during the fabrication is required for better EMI shielding. New nano-fillers such as functionalization and composite polymers are best to enhance the EMI shielding and conductive properties. Â© 2021 Elsevier Inc.